Role of Grain Boundary Character Distribution on Tensile Properties of 304L Stainless Steel - Bandari Ravi Kumar; Ghosh Chowdhury, Sandip; Narasaiah, N.; Mahato, B.; Das, S.K. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2007)
This work describes the effect of thermomechanical processing (TMP) on grain boundary character distribution (GBCD) and the effect of GBCD on tensile properties of 304L austenitic stainless steel. The material was solution treated before the TMP. Electron back-scattered diffraction and tensile properties evaluation were carried out. The tensile properties were found to vary with the processing conditions. The percent elongation and strain hardening exponent of the thermomechanically processed material was found to be larger than that of the starting material. The increase in the percent elongation was correlated with special coincidence boundaries. On the other hand, the strain hardening exponent was observed to be influenced by the type of texture developed from the TMP. [PUBLICATION ABSTRACT]